Research of microorganisms indicating hygienic-sanitary quality in express ice cream in the City of Mossoró, Rio Grande do Norte, Brazil (Research, Society and Development, 2021)
Ice cream is a highly consumed food in Brazil and worldwide and can be produced from milk and eggs. These raw materials are very susceptible to microbial degradation and can cause Foodborne Diseases in consumers. Thus, the objective of this work was to evaluate the hygienic-sanitary quality of ice cream express in the city of Mossoró, Rio Grande do Norte. Microbiological analyzes of total and thermotolerant coliforms were carried out in ten samples of ice cream express. All samples were positive for the presence of total coliforms. Of the ten samples studied, nine confirmed the presence of thermotolerant coliforms when incubated in Escherichia coli (EC) broth. Simmons' Citrati biochemical test was applied among the positive samples for thermotolerant coliforms, one with a confirmatory result. Thus, for this product to be suitable for commercialization and consumption, the participation of Organs competent bodies that work in the continuous inspection of the entire food production process is necessary, in order to comply with current legislation and maintain quality control for the consumer.